The Impact of Debt Service in Stimulating Economic Growth in Nigeria: Mediating on its role on Public Sector Financial Management: Array - Olusegun, Efuntade Alani; Oladipo, Olaniyan Niyi; Omotayo, Efuntade Olubunmi Omotayo (Acta Universitatis Danubius. Œconomica, 2021)
The study examined debt service and its impact on economic growth of the country. It specifically examined the impact of debt servicing on economic using its role on public sector financial management as a mediating factor. The study predicted on dependency theory, Keynesian theory and neoclassic theory. Secondary data source was explored in presenting the facts of the situation. The secondary data were obtained from the debt management office which covered the period of 30 years spanning from 1990-2020. Data collated were analyzed using both descriptive and covariance estimate method of analysis. Descriptive analysis conducted in the study include the mean, standard deviation, Kurtosis, and Jarque-Bera statistics of each variable. The findings revealed among other things that; there was presence of co-integration (long-run relationship) among the dependent and all the explanatory variables which is a clear indication that working debt servicing has positive and significant impact on economic growth of the country both in short and long run if properly managed. It was concluded that debt servicing has significant impact on the economic growth due to his positive relationship with gross domestic product, while exchange rate reflected a negative significant relation to Gross domestic product. This study recommends among others that government should ensure that any debt both internal and external debt should be deal that will open Nigeria to greater trade and investment and can stimulate the economic growth of the country.